2021
DOI: 10.1371/journal.pone.0247010
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Helicobacter infection and associated mortalities in endangered Grand Cayman blue iguanas (Cyclura lewisi) and introduced green iguanas (Iguana iguana)

Abstract: The Blue Iguana Recovery Programme maintains a captive breeding and head-starting program for endangered Grand Cayman blue iguanas (Cyclura lewisi) on Grand Cayman, Cayman Islands. In May 2015, program staff encountered two lethargic wild Grand Cayman blue iguanas within the Queen Elizabeth II Botanic Park (QEIIBP). Spiral-shaped bacteria were identified on peripheral blood smears from both animals, which molecular diagnostics identified as a novel Helicobacter species (provisionary name Helicobacter sp. GCBI1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Also, our culture and PCR results indicated that H. cyclurae was more commonly identified in the feces and cloacal samples from clinical normal animals in our study compared with Helicobacter sp. GCBI1 identified in clinically ill iguanas in blood and tissue samples (Conley et al, 2021). In our previous study, clinically ill blue iguanas who developed lethargy, weakness, inappetence, and septicemia had spiral-shaped bacteria identified on peripheral blood smears (Conley et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Also, our culture and PCR results indicated that H. cyclurae was more commonly identified in the feces and cloacal samples from clinical normal animals in our study compared with Helicobacter sp. GCBI1 identified in clinically ill iguanas in blood and tissue samples (Conley et al, 2021). In our previous study, clinically ill blue iguanas who developed lethargy, weakness, inappetence, and septicemia had spiral-shaped bacteria identified on peripheral blood smears (Conley et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…GCBI1 identified in clinically ill iguanas in blood and tissue samples (Conley et al, 2021). In our previous study, clinically ill blue iguanas who developed lethargy, weakness, inappetence, and septicemia had spiral-shaped bacteria identified on peripheral blood smears (Conley et al, 2021). Through 16S rRNA genespecific primers, Helicobacter spp.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations